IMPLEMENTASI KEBIJAKAN PEMBELAJARAN TARI DI SEKOLAH ISLAM SMA IT AL-KHOLIS - Ayu Aprilliani, Niken; Habsary, Dwiyana; Kurnia Adzan, Nabilla (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of dance learning policy at SMA IT Al-Kholis. Dance education in Islamic schools requires adjustments to ensure alignment with the religious principles upheld by the institution. This research employed a qualitative approach with a descriptive research design. The research subjects included the principal, the vice principal for curriculum affairs, and the arts and culture teacher. Data collection techniques consisted of semi-structured interviews, observation, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, with data validity ensured through source and method triangulation. The results indicate that the implementation of the dance learning policy at SMA IT Al-Kholis has been carried out in accordance with the characteristics of an integrated Islamic school. Based on the policy implementation theory of Donald Van Meter and Carl Van Horn, the success of implementation is influenced by six main variables: (1) clearly defined policy standards and objectives articulated in the school’s vision and mission; (2) the availability of resources, including teachers with basic instructional competencies and supporting facilities; (3) the characteristics of implementing agents who possess religious competence aligned with the Islamic school context; (4) effective communication among school stakeholders and the foundation; (5) positive attitudes of implementers who support dance learning as an educational medium; and (6) a religious social and cultural environment that remains supportive of dance education. Thus, dance learning in the school is positioned as a means of character building and fostering students’ creativity.